Characteristics of stakeholder involvement in systematic and rapid reviews: a methodological review in the area of health services research - Milo Alan Puhan; Jonas Feldmann; Margot Mütsch (BMJ Open)
Objective Engaging stakeholders in reviews is considered to generate more relevant evidence and to facilitate dissemination and use. As little is known about stakeholder involvement, we assessed the characteristics of their engagement in systematic and rapid reviews and the methodological quality of included studies. Stakeholders were people with a particular interest in the research topic.Design Methodological review.Search strategy Four databases (Medline, Embase, Cochrane database of systematic reviews, databases of the University of York, Center for Reviews and Dissemination (CRD)) were searched based on an a priori protocol. Four types of reviews (Cochrane and non-Cochrane systematic reviews, rapid and CRD rapid reviews) were retrieved between January 2011 and October 2015, pooled by potential review type and duplicates excluded. Articles were randomly ordered and screened for inclusion and exclusion criteria until 30 reviews per group were reached. Their methodological quality was assessed using AMSTAR and stakeholder characteristics were collected.Results In total, 57 822 deduplicated citations were detected with potential non-Cochrane systematic reviews being the biggest group (56 986 records). We found stakeholder involvement in 13% (4/30) of Cochrane, 20% (6/30) of non-Cochrane, 43% (13/30) of rapid and 93% (28/30) of CRD reviews. Overall, 33% (17/51) of the responding contact authors mentioned positive effects of stakeholder involvement. A conflict of interest statement remained unmentioned in 40% (12/30) of non-Cochrane and in 27% (8/30) of rapid reviews, but not in Cochrane or CRD reviews. At most, half of non-Cochrane and rapid reviews mentioned an a priori study protocol in contrast to all Cochrane reviews.Conclusion Stakeholder engagement was not general practice, except for CRD reviews, although it was more common in rapid reviews. Reporting factors, such as including an a priori study protocol and a conflict of interest statement should be considered in conjunction with involving stakeholders.